KARAKTERISTIK KEKUATAN TARIK KOMPOSIT BERPENGUAT SERAT AMPAS TEBU DENGAN MATRIKS EPOXY - Catur Pramono; Sri Widodo; Muhamad Galih Ardiyanto (Journal of Mechanical Engineering, 2019)
Composite is a material consisting of two or more components which have characteristics mild and relatively strong. This study used bagasse fiber which is widely produced in sugar industry. Treatment of bagasse fiber by soaked in alkaline solution (NaOH) for 2 hours to remove the cork / wax attached to the fiber. Manufacture of composite by hand lay up. The matrix used in this study is epoxy. The fraction volume of composite between bagasse fiber and epoxy are 4%: 96%, 8%: 92% and 12%: 88%. The mechanical properties tested is tensile strength. The tensile test refers to ASTM D638 type 4. The highest tensile test composite resulted at the fraction volume composite of bagasse fiber with epoxy 12%: 88% i.e. 28.43 MPa.